Aplikasi Pengenalan Wajah dengan Metode Adaptive Resonance Theory (ART) - Devira Frenza; Riki Mukhaiyar (Dinasti Research, 2021)
Image processing technology (image processing) at this time can be done using a computer. An image that can be recognized by a computer is called a digital image. One application of image processing (image processing) is the field of face detection (face detection). Today's face detection system is one of the most important technologies. Because, facial recognition systems are closely related to security systems, where facial recognition systems can be applied in various places and situations, namely: security system applications, facial disguise recognition applications, and database information system applications for an institution. In this study, we will discuss facial recognition using the Principal Component Analysis (PCA) method and the Artificial Neural Network (ANN) used is Adaptive Resonance Theory (ART). The application used to conduct this research is Matlab.